Thyroglossal duct cyst: myriad presentations - Meenakshi, S.; Rajasekar, M. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Thyroglossal duct cysts are the most common midline neck swellings. They are routinely treated by surgeons with simple excision. Methods: We present a retrospective study of a series of 30 cases operated in our hospital over a period of five years and the challenges faced during investigations, surgery and postoperative period. All patients were clinically diagnosed as thyroglossal duct cysts. The diagnosis confirmed with USG Neck and FNAC of the swelling. CECT NECK was used to delineate the normal thyroid and patients were subjected to Sistrunk procedure under general anesthesia. Results: The outcome of all cases was good with one case being a revision surgery and another case going in for delayed healing due to infection. All patients were healthy with no complaints postoperatively. Conclusions: This study validates the Sistrunk surgery as the best method of excision to avoid recurrences. This article highlights the variant presentations of this cyst in our institution and the challenges we faced in diagnosis, during surgery and later as well.